Streptococcus pneumoniae serotype 15B polysaccharide conjugate elicits a cross-functional immune response against serotype 15C but not 15A. Issue 33 (5th August 2022) - Hao, Li; Kuttel, Michelle M.; Ravenscroft, Neil; Thompson, Allison; Prasad, A. Krishna; Gangolli, Seema; Tan, Charles; Cooper, David; Watson, Wendy; Liberator, Paul; Pride, Michael W.; Jansen, Kathrin U.; et al.
Abstract: Protection conferred by pneumococcal polysaccharide conjugate vaccines (PCVs) is associated with PCV-induced antibodies against vaccine-covered serotypes that exhibit functional opsonophagocytic activity (OPA). Structural similarity between capsular polysaccharides of closely related serotypes may result in induction of cross-reactive antibodies with or without a cross-functional activity against a serotype not covered by a PCV, with the former providing an additional protective clinical benefit. Serotypes 15B, 15A, and 15C, in the serogroup 15, are among the most prevalent Streptococcus pneumoniae serotypes associated with invasive pneumococcal disease following the implementation of a 13-valent PCV; in addition, 15B contributes significantly to acute otitis media. Serological discrimination between closely related serotypes such as 15B and 15C is complicated; here, we implemented an algorithm to quickly differentiate 15B from its closely related serotypes 15C and 15A directly from whole-genome sequencing data. In addition, molecular dynamics simulations of serotypes 15A, 15B, and 15C polysaccharides demonstrated that while 15B and 15C polysaccharides assume rigid branched conformation, 15A polysaccharide assumes a flexible linear conformation. A serotype 15B conjugate, included in a 20-valent PCV (PCV20), induced cross-functional OPA serum antibody responses against the structurally similar serotype 15C but not against serotype 15A, both not included in PCV20. In PCV20-vaccinated adults (18–49 years), robust OPA antibody titers were detected against both serotypes 15B (the geometric mean titer [GMT] of 19, 334) and 15C (GMTs of 1692 and 2747 for strains PFE344340 and PFE1160, respectively), but were negligible against serotype 15A (GMTs of 10 and 30 for strains PFE593551 and PFE647449, respectively). Cross-functional 15B/C responses were also confirmed using sera from a larger group of older adults (60–64 years).